Hubungan Tata Kelola Data dan Kualitas Data pada Sistem Informasi Akuntansi: Studi Literatur - Asen Devito Hutabarat; Markus Robin Harefa; Rafli Faturrahman (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the relationship between data governance and data quality in Accounting Information Systems (AIS) using a literature review approach. Data quality is a crucial factor in producing relevant, reliable, and accurate accounting information, while data governance acts as a control and regulatory mechanism that ensures data is managed according to the principles of accuracy, consistency, integrity, and security. This article reviews national and international literature highlighting the role of data governance in improving data quality, particularly in the implementation of AIS in both public and private sectors. The findings indicate that effective data governance enhances data quality dimensions such as accuracy, completeness, relevance, and timeliness. Therefore, data governance has significant implications for the effectiveness of AIS in supporting decision-making processes and financial reporting.